AI Image Generator in Digital Illustration Creation: A Literature Review - Herliyani, Elly; Agustini, Ketut; Sudatha, I Gde Wawan; Dantes, Gede Rasben; Suharta, I Gusti Putu; Suartama, I Kadek (International Journal of Artificial Intelligence Research, 2024)
The use of artificial intelligence image generators in creating digital illustration is experiencing rapid development as an alternative to support the work of designers in  various fields, especially visual communication design. Despite its sophistication, we must consider some aspects of the human side in order to maximize the  design aesthetic value. This research aims to find out what applications are used in the AI image generator, as well as to identify the results of digital illustrations using the AI image generator. The results of this research show that the image generation diffusion model with various techniques and variations developed can produce excellent and unique text-based quality and control. However, humans are still the best pilots for determining text-based commands that can produce and function the greatest result.